ANALISIS KESULITAN SISWA PADA MATERI BANGUN RUANG SISI DATAR - Murni Chintia; Risma Amelia; Nelly Fitriani (IKIP Siliwangi, 2021)
This research was conducted with the aim of analyzing the difficulties experienced by students in working on BRSD material problems. This is taken from the cognitive indicators on the bloom taxonomy which are indicators of its difficulty. This research uses a qualitative descriptive method. The data collection technique is by giving questions to students. Furthermore, students' answers are analyzed to determine the extent of the difficulties that occur to students based on the determined indicators. This research was conducted at one of the state junior high schools in Cimahi for the 2020-2021 academic year. The subjects were 20 grade IX students. The instrument inside is a test item with predetermined indicators. The results of the analysis obtained are that there are still students who have difficulty solving indicators of problems that involve cubes. The above is evidenced by the results of the test questions to students where 70% of students experience difficulties with the question indicators as well as the percentage of student answers that are less than the predetermined KKM. The factors that make this indicator experience difficulties are (1) the students' lack of thoroughness in reading, understanding and answering questions; (2) Lack of students' spatial ability to imagine BRSD; (3) Students are accustomed to solving routine problems found in examples.